How dare you think divergently! - The novel thoughts of Kant and the Rationalists and the restrictive politico-religio-theological framework in the seventeenth and eighteenth centuries - Helenius Visa (the Donner Institute, 2025)
Freethinking seems to be desirable because the human being is seen as an independently thinking being. However, as is well known, freethinking should not be taken forgranted: ideological indoctrination, manipulation and propaganda, inter alia, are versatile tools for rulers and, in consequence, regularly repeated phenomena. One of the most drastic intellectual turning points in history occurred in the seventeenth and eighteenth centuries, when the incontestable religious world view of European civilization changed along with early modern science and the Age of Enlightenment. Although freethinking and religion do not have to be thought of as opposed, the period in question includes instances of complex and delicate phenomena, which in this article are termed intellectual purism and socio-intellectual control. The discussion includes how five thinkers (Descartes, Spinoza, Leibniz, Wolff, Kant) operated in a restrictive politico-religio-theological framework and how they manifest religious deviance.